Diagnóstico del sistema de flotación en la planta pp5y su influencia en las pérdidas de energía eléctrica en la empresa grupo familia de la ciudad de Latacunga en el año 2015 automatización del sistema de flotación en la planta pp5. - Tacan Santamaria, Juan Xavier (2017)
The present investigation of the automation of the process of the destination by the flotation in the plant of the paste PP5 new technologies to reduce the consumption of electrical energy in the company Group Family, with the purpose of potentializing the use of the current technologies, replacing old controls; reducing energy consumption, increasing profitability and achieving business sustainability. The development of the present work takes into account the guidelines that are established in the process of justifying business projects, especially those focused on income. The object of analysis is the study of the loss of electrical energy in the process of destination of the PP5 pulp plant, which is carried out through field measurements and through a detailed study using scientific research methods quantitative and experimental. Identifies the origin of the current situation of the area; opportunities are also detected from the technological point of view, which are properly selected and implemented. As a result of this analysis and the implementations was obtained in the first instance the calculated results and finally the experimental results, of definitive electrical energy; which are duly registered and controlled. Finally, the basic economic evaluation TIR and VAN are carried out; with figures that meet business expectations.